Juncture-Verb Constructions in Northeastern Kalahari Khoe: A comparative perspective - Fehn, Anne-Maria; Phiri, Admire (Stellenbosch Papers in Linguistics Plus, 2022)
Multiverbal predicates constitute a defining feature of the Kalahari Basin linguistic area of southern Africa encompassing the Kx’a, Tuu, and Khoe-Kwadi language families. Here, we focus on a complex predicate type restricted to the Khoe-Kwadi family’s Khoe branch which involves a linker morpheme and is thus referred to as Juncture-Verb Construction (JVC). While JVCs have synchronically been interpreted as Serial Verb Constructions (SVC), their origin and relationship with SVCs in the narrower sense as found in the Kx’a and Tuu families remain debated. The Kalahari Khoe languages Ts’ixa, Shua and Northern Tshwa spoken along the northeastern Kalahari Basin fringe present a convenient case study to expand the descriptive corpus on Khoe JVCs while addressing the limits of areal spread and contact influence. We show that all languages under consideration present JVCs with formal and functional properties corresponding to those found in other Kalahari Khoe languages, while also sharing features with SVCs as attested in the Kx’a and Tuu families. Both JVCs and SVCs contrast with conjoined predicates and are defined by single-eventhood. JVCs cover the same semantic domains found among SVCs of the Kx’a and Tuu families, can be subdivided into symmetrical and asymmetrical constructions, and show the same potential for lexicalization and grammaticalization, respectively.